De homeostatische bevolkingsreeks voor Amsterdam in 1586-1865 toegelicht en getoetst - Nusteling, Hubert (TSEG - The Low Countries Journal of Social and Economic History, 2018)
The contribution concerns the homeostatic method, as applied for construing an Amsterdam population series from 1586 to 1865,  and the criticism which it received. The method has been based on extrapolation of population numbers from one interval with a known population total (count) to another with the use of a series of fertile marriages. So, it implies that, in the Ancient Regime, an almost constant relationship existed between successive generations of married women in their fertile years (weighted fertile marriages) and the size of the population, to which they belonged. Due to changing quotes of remarriages as a consequence of changing mortality, series of first marriages are preferred. Whatsoever the causes of differences or divergences between marriage series may be, adequate corrections are required for applying different series successively.  When combined, they ought to be consistent. The critics, however, totally neglect this prescript. Accordingly, it  is no wonder that the population numbers they present as a better alternative for the homeostatic series, in general do not include  results of a higher quality than earlier published estimates, while the homeostatic method just scores definitely better.